CRISPR-Cas, a Revolution in the Treatment and Study of ESKAPE Infections: Pre-Clinical Studies - Manuel González de Aledo; Mónica González-Bardanca; Lucía Blasco; Olga Pacios; Inés Bleriot; Laura Fernández-García; Melisa Fernández-Quejo; María López; Germán Bou; María Tomás (Antibiotics, 2021)
One of the biggest threats we face globally is the emergence of antimicrobial-resistant (AMR) bacteria, which runs in parallel with the lack in the development of new antimicrobials. Among these AMR bacteria pathogens belonging to the ESKAPE group can be highlighted (Enterococcus spp., Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter spp.) due to their profile of drug resistance and virulence. Therefore, innovative lines of treatment must be developed for these bacteria. In this review, we summarize the different strategies for the treatment and study of molecular mechanisms of AMR in the ESKAPE pathogens based on the clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated (Cas) proteins’ technologies: loss of plasmid or cellular viability, random mutation or gene deletion as well directed mutations that lead to a gene’s loss of function.